1995
DOI: 10.1046/j.1471-4159.1995.64031216.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Catalase Activity but Unchanged Superoxide Dismutase Activity in Brains of Patients with Dementia of Alzheimer Type

Abstract: “Oxidative stress” may be of significance in the etiopathogenesis of dementia of Alzheimer type (DAT). Therefore, we measured activities of the enzymes superoxide dismutase (SOD) and catalase (CAT), which detoxicate reactive oxygen species. Enzyme activities were measured postmortem in basal ganglia, cortical, and limbic brain regions of patients with DAT and age‐matched controls. SOD activity increased with age in basal nucleus of Meynert. However, there was no significant difference in SOD activity between D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(56 citation statements)
references
References 27 publications
6
49
0
1
Order By: Relevance
“…Several studies have reported the reduction of SOD in the frontal cortex of AD patients (40), whereas a slight elevation of SOD was demonstrated in the caudate nucleus of AD patients (41). Alternatively, other researchers have suggested that no changes in SOD levels are seen in AD brains (42). Recently, Ansari and Scheff (43) reported a strong correlation between oxidative damage levels (total SOD, GSH, catalase, thiobarbituric acid reactive substances, protein carbonyl, 3-nitrotyrosine, 4-hydroxynonenal, and acrolein) and the variable dementia status of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the reduction of SOD in the frontal cortex of AD patients (40), whereas a slight elevation of SOD was demonstrated in the caudate nucleus of AD patients (41). Alternatively, other researchers have suggested that no changes in SOD levels are seen in AD brains (42). Recently, Ansari and Scheff (43) reported a strong correlation between oxidative damage levels (total SOD, GSH, catalase, thiobarbituric acid reactive substances, protein carbonyl, 3-nitrotyrosine, 4-hydroxynonenal, and acrolein) and the variable dementia status of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Kunz and colleagues showed that SOD activity was increased only in acute phases of BD with no significant difference between euthymic BD and controls [42], which may be linked to a compensatory mechanism in response to ROS overproduction during an acute episode, activating additional mechanisms of neuronal plasticity, such as the anti-oxidative defense systems like SOD [43].…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
“…Accumulation of damaged, oxidized, dysfunctional protein seems to result from a combination of age related increase in the rate of oxygen free radical mediated damage and a loss of the ability to degrade oxidized protein (Facchini et al 2000). Indeed increased levels of oxidized protein and reduced activity of antioxidant enzymes have been demonstrated in the brains of aged individuals with and without AD (Gsell et al 1995;Troni et al 1984), and in diabetes (Table 4).…”
Section: Diabetic Neuropathy-peripheral and Central Nervous Systemmentioning
confidence: 99%